Prussian blue as a co-catalyst for enhanced Cr(vi) photocatalytic reduction promoted by titania-based nanoparticles and aerogels - Ferreira-Neto, Elias Paiva [UNESP]; Ullah, Sajjad [UNESP]; Perissinotto, Amanda Pasquoto; Vicente, Fabio S. de [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Worsley, Marcus Andre; Rodrigues-Filho, Ubirajara Pereira (Royal Soc Chemistry, 2021)
Hexavalent chromium (Cr(vi)) is an noxious and highly toxic heavy metal that presents a serious threat to human health if present even in low concentrations in drinking water. Photocatalytic reduction of Cr(vi) to its less toxic Cr(iii) state is a potential strategy to combat Cr(vi) pollution, but the efficiency of the process is low, especially in the absence of hole scavenger organic reagents. To address this issue and prepare efficient photocatalysts for Cr(vi) removal from water, in this study, we explored Prussian blue (PB) as a co-catalyst for improving the photoreduction performance of different high surface area TiO2-based materials (titania or silica-titania nanoparticles and aerogels). The photocatalyst nanomaterials were surface-modified with nanocrystalline PB using the photodeposition route. The PB layer acts as an effective electron acceptor/mediator between the semiconductor photocatalyst and Cr(vi) species. All the PB-modified photocatalysts exhibit higher photocatalytic activity (up to 9 times faster) as compared to the unmodified photocatalysts towards reduction of Cr(vi). Importantly, the PB-modified photocatalysts exhibited high photocatalytic performance (98-99% reduction in 40 min for pH = 5.6 and in 10 min for pH = 3) without addition of organic reagents. The simple approach reported herein can be followed to prepare new PB-photocatalyst systems with improved photocatalytic performance towards Cr(vi) reduction and other target applications.